DESIGN CHARACTERISTICS OF WILD WEST COSTUME AND ITS INFLUENCE ON MODERN FASHION TRENDS - Чупріна, Н. В.; Давиденко, І. В.; Кудрявцева, Н. І.; Данилюк, О. В. (Art and Design, 2021)
Purpose. Identification patterns of evolution of the design image of the cowboy in the crisis of masculinity in popular culture during the twentieth century and its impact on modern fashion trends. Methodology. Literary-analytical and comparative methods of research of the original source are used to determine the aesthetic, design and artistic characteristics of the image; stylistic and compositional analysis of modern fashion trends based on the adaptation of the design characteristics of the image of a cowboy in the design of the suit is committed. Results.It is established that the image and symbol of the cowboy in world culture has a significant impact on the trends of men's and women's fashion both during the twentieth century and today. This influence is due to a number of social, economic and environmental factors, the coherence of which creates an aesthetic and figurative need to return the image of the cowboy as a role model in society and as a symbol in culture, art and design. The principles of introduction of artistic and compositional components of the image of a cowboy in modern collections of a suit in a segment of mass fashion are characterized. The means of spreading the idea of smart consumerism and renovation of textiles in the design of fashionable clothes are determined. Based on the pre-project analysis, the figurative and artistic interest in the adaptation of the properties of clothing in the style of "western" to the formation of the individual wardrobe of the consumer is determined. The design concept is formed and the structure of the corresponding collection for wide layers of consumers of clothes as a product of fashion is developed. The scientific novelty. Identification of the main design and artistic characteristics of the historical costume of the Wild West and their transformation in the development of image-compositional structure of the costume in modern fashion. The elements of sign-information stylistics of this project image are revealed and their influence on modern fashion tendencies in both men's and women's fashion is determined. Approaches to the design and artistic modeling of women's clothing as a fashion product based on the renovation of textile products are identified. The practical value. The significance is due to the possibility of using the results of research in the design of clothing for men and women in retro and eco-style "western", taking into account current fashion trends, as well as the ability to predict the further development of the cowboy image in mass culture and its influence on fashion trends